Caving, Seismicity, and Mine Design in Four Utah Mines - Hamid Maleki (International Conference on Ground Control in Mining, 2006)
Having developed a methodology for estimating mining-induced seismicity resulting from slip along geological discontinuities in 2003, in this paper, the importance of measurements are high-lighted in the study of caving and seismic source mechanisms as applied to mine designs. Geotechnical data is analyzed from four case studies to address cave condition, load transfer, and potential effects on stability and resource recovery in four Utah mines using measurements and observations conducted over the last three decades. Cave conditions are evaluated on the basis of measurements in the gob of a western U.S. operation mining under the massive Castlegate Sandstone and indirectly using the results of measurements and boundary-element modeling at panel boundaries at a mine where strata behave elastically. Together with subsidence measurements and microseismic monitoring, regional caving and load transfer in multiple-panel extractions are addressed while the effectiveness of barrier pillars in reducing stress and seismic response where mining under massive stratigraphic units is analyzed using measurements and three-dimensional computer modeling.